2010
DOI: 10.1002/jmv.21722
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 primary and secondary antiretroviral drug resistance and genetic diversity among pregnant women from central Brazil

Abstract: Antiretroviral (ARV) resistance mutations in HIV-1 may reduce the efficacy of prophylactic therapy to mother-to-child transmission and impact future treatment options. ARV resistance mutations and HIV-1 phylogenetic diversity in protease (PR) and reverse transcriptase (RT) genes were assessed among 77 pregnant women (35 naïve, 42 treated with ARV) from Goiânia/Goiás, central west Brazil. ARV mutations in PR/RT genes were analyzed against the Stanford Database, PR/RT HIV-1 subtypes were assigned by phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
0
23
1
2
Order By: Relevance
“…This and other neighboring countries, such as Argentina, along with most Brazilian cities, had shown only sporadic identification of clade C. 2,7 In central Brazil, clade C has been reported in a few cases, below 4%. 3 In Rio de Janeiro a study at a local blood bank identified one sample (1.4%) of a BC mosaic. 12 In Sã o Paulo, a study from our group identified a low proportion (0.5%) in samples from 1998-2003, which represented 2.3% if only ARV-naive cases were considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This and other neighboring countries, such as Argentina, along with most Brazilian cities, had shown only sporadic identification of clade C. 2,7 In central Brazil, clade C has been reported in a few cases, below 4%. 3 In Rio de Janeiro a study at a local blood bank identified one sample (1.4%) of a BC mosaic. 12 In Sã o Paulo, a study from our group identified a low proportion (0.5%) in samples from 1998-2003, which represented 2.3% if only ARV-naive cases were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Non-B non-F variants are occasionally observed. 3,6,7 In this study, we evaluated the presence and growth trends of HIV-1 C in Sã o Paulo and Campinas, the two largest metropolitan areas of Sã o Paulo state.…”
Section: Introductionmentioning
confidence: 99%
“…1). [2][3][4][5] However in the Southern region, a distinct profile is observed. Currently, depending on the state, 27-79% of HIV infections are caused by HIV-1C, 23-45% by HIV-1B, 3-29% by CRF31 BC and other BC recombinants, and HIV-1F and its recombinants account for up to 10% of infections.…”
Section: Introductionmentioning
confidence: 89%
“…2,3 In Brazil, the major circulating HIV-1 subtype is B (HIV-1B), yet other subtypes such as A1, C, D, F1, BF1, and BC recombinants have also been found. [4][5][6][7] The southern region of Brazil is unique, with an endemicity of HIV-1 subtype C (HIV-1C). Several studies have reported an increase in HIV-1C prevalence in that region.…”
Section: Introductionmentioning
confidence: 99%